2013
DOI: 10.1002/chem.201301522
|View full text |Cite
|
Sign up to set email alerts
|

The Redox‐Neutral Approach to CH Functionalization

Abstract: The direct functionalization of C-H bonds is an attractive strategy in organic synthesis. Although several advances have been made in this area, the selective activation of inert sp(3) C-H bonds remains a daunting challenge. Recently, a new type of sp(3) C-H activation mode through internal hydride transfer has demonstrated the potential to activate remote sp(3) C-H linkages in an atom-economic manner. This Minireview attempts to classify recent advances in this area including the transition to non-activated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(63 citation statements)
references
References 100 publications
2
57
0
2
Order By: Relevance
“…[13a] However, one of the main challenges associated with this approachi st he inherent low reactivity of C À H bonds, [15] which entails that harsh reactionc onditions are often required to provide the target products in synthetically useful yields. [16] Furthermore,r egioselectivity is an integral challenge when several similarC À Hb onds exist in the same molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[13a] However, one of the main challenges associated with this approachi st he inherent low reactivity of C À H bonds, [15] which entails that harsh reactionc onditions are often required to provide the target products in synthetically useful yields. [16] Furthermore,r egioselectivity is an integral challenge when several similarC À Hb onds exist in the same molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Aus mechanistischer Sicht komplett verschieden ist eine Klasse von üblicherweise redoxneutralen C-H-Funktionalisierungen, die eine intramolekulare Hydridverschiebung als Schlüsselschritt einschließen. Solche Reaktionen sind das Thema dieses Aufsatzes, in dem wir Fortschritte seit dem Erscheinen der letzten Übersicht [18] zu Aspekten dieses Gebiets im Jahr 2006 präsentieren. Außerdem nehmen wir Bezug auf wichtige historische Beispiele für diese Reaktionen, die weder in früheren Übersichten noch in jüngeren Verçffentlichungen ausführlich diskutiert worden sind.…”
Section: Introductionunclassified
“…(3)],t hus indicating that the reaction pathway involving double [1,5] hydride shift is less likely (Scheme 3, path b). [17] In particular,itwas found that the ketene aminal 11 f [13,18] could be readily converted into the corresponding 2f when subjected to yttrium catalysis,t hus strongly supporting that [3,3] rearrangement was presumably involved in such atandem process [Eq. (4)].…”
mentioning
confidence: 96%